Potentiation of azaserine by cholestyramine in the rat. - Morgan, R. G. (1990)
In the rat, when pancreatic growth is stimulated there is an increased incidence of spontaneous pancreatic neoplasms and marked potentiation of the pancreatic carcinogen azaserine. Since previous studies showed that cholestyramine caused pancreatic growth in this species we have now studied the effect of azaserine in rats fed soya flour diets containing cholestyramine. Two groups, each of eight rats, were fed either heated soya flour (HSF) or raw soya flour (RSF). Two further groups, each of 12 rats, received the same diets containing 2% cholestyramine (HSF + C, RSF + C). In each group, four rats received azaserine (30 mg/kg i.p.) and the remainder saline, weekly, for the first 5 weeks. Animals were killed after 24 weeks and pancreatic growth and the number and size of pancreatic neoplastic nodules was measured. RSF caused a significant increase in pancreatic weight, protein, RNA and DNA, compared with HSF and cholestyramine caused a further significant increase in pancreatic weight, protein and RNA but not DNA. Azaserine did not affect pancreatic growth. In azaserine-injected rats significantly more nodules were seen and the nodules were larger and the tumour burden greater in rats fed HSF + C than in rats fed HSF alone. However, the nodule count and other nodule parameters were not significantly different in RSF and RSF + C fed rats. It is concluded that 2% cholestyramine enhances pancreatic growth when added to soya flour diets and in rats fed HSF it potentiates the action of azaserine on the pancreas. It does not increase the potentiation of azaserine seen with RSF up to 24 weeks.